Phytotherapy in diabetes: a review of plant - Monika Kuc; Katarzyna Cyboran; Damian Machaj; Tomasz Korzec; Konrad Kania (Kazimierz Wielki University, 2021)
More than 200 species of plants possess antidiabetic properties which were evaluated mostly by screening tests without digging far for the exact mode of action. Searching among the different literature resources and various database, this  article provides a comprehensive review on the available antidiabetic plants that have been approved by pharmacological and clinical evaluations, and which their mechanism(s) of action is assured.